REPORT FROM THE FIELD: THE POWER OF FIRST VOICE ADVOCACY: RALLYING LIVED EXPERTISE TO SUPPORT EQUITABLE TRANSITIONS TO ADULTHOOD FOR YOUTH IN CARE IN CANADA - Doucet, Melanie; Bach, Ashley; Christian, Marie (International Journal of Child, Youth and Family Studies, 2023)
This report describes a national lived experience advocacy movement generated by the work of the National Council of Youth in Care Advocates to support equitable transitions to adulthood for youth in care in Canada. The emergence of the National Council at the beginning of the COVID-19 pandemic is presented, as well as the ongoing progress and achievements in advocacy and best practice efforts at the national and local jurisdiction levels. This article, by three members of the National Council, is the first to provide an account of the process associated with national lived experience advocacy mobilization by and for youth in care.